A 87 YEARS OLD MALE WITH GIANT PROSTATIC HYPERPLASIA AND BLADDER STONES, THE LARGEST PROSTATE REPORTED IN INDONESIA - Vera, Vera; Pramod, Sawkar Vijay (Indonesian Urological Association, 2017)
Objective: The aim of this article is to report a case of Giant Prostatic Hyperplasia and see the correlation between volume of prostate and benign prostate hyperplasia (BPH) symptoms. Giant BPH is defined as a prostate weight over 200 g or 500 g; the lower threshold was suggested by Japanese authors. It’s extremely rare, with only 16 cases exceeding 500 g till 2013. Case presentation: Patient was an 87-year-old male with chief complaint of haematuria. We performed Transabdominal Ultra Sonography (USG) on the patient. Discussion: Transabdominal USG showed enlarged prostate with median lobe protruding into the bladder measuring 86 x 102 x 76 mm and 348 cc in volume. We performed transvesical prostatectomy. The large prostate was enucleated completely in one piece with 23 stones measuring about 1 cm in size. Grossly, the mass measured 12 x 8 cm and weighed 300 g. Histopathology evaluation revealed BPH. Conclusion: To our knowledge, this is the first giant BPH case being reported in Indonesia. We would like to emphasize that severity of BPH symptoms does not correlate with volume of the prostate. Unfortunately, we can not conclude that there were correlation between body mass index (BMI) and volume due to lack of BMI data from the literature.